The Influence of Accounting and E-Commerce Information Systems on MSME Performance in the City of Surabaya - Ramadhana, Nabilah Dita; Handayani, Susi (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study examines how accounting information systems and e-commerce adoption affect the operational performance of MSMEs. As digital transformation and efficient financial reporting become increasingly important for business sustainability, this study investigates their role in enhancing MSME growth. Using a quantitative approach, this study collected data through a survey distributed to MSME owners in Surabaya, Indonesia. Multiple linear regression analysis, conducted using SPSS, showed that a robust accounting system significantly improved market expansion and sales performance. The findings highlight that the integration of digital tools in financial management and the utilization of e-commerce platforms can improve operational efficiency, accuracy, and overall competitiveness for MSMEs in today’s digital economy.